Modeling and Simulation of 127 Level Optimal Multilevel Inverter with Lower Number of Switches and Minimum THD - Bolla Madhusudana Reddy; Y. V. Siva Reddy; M. Vijaya Kumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper proposes a new optimal high level multilevel inverter with minimum number of components. This multi level inverter (MLI) is designed with series combination of basic units which can generate positive levels at output. DC source values applied for each basic unit is different with another. An H bridge is connected across proposed MLI for generating negative levels along with positive levels at output and that inverter considered as proposed high level optimal multilevel inverter. Single unit is responsible producing 21 levels. Therefore six units are connected in cascaded form to increase number of levels as 127 at output. Decrease in the number of power switches, driver circuits, and dc voltage sources are the improvement of the proposed MLI. Sinusoidal multiple pulse width modulation (SPWM) technique is implemented to produce pulses for turning ON switches according requirement. Low total harmonic distortion at output voltage or current production is major advantage of proposed module. The validations of proposed MLI results are verified through MATLAB/SIMULINK.